Lithium: A therapeutic option in Alzheimer's disease and its prodromal stages?. (24th August 2021) - Haussmann, Robert; Noppes, Felix; Brandt, Moritz D.; Bauer, Michael; Donix, Markus
Highlights: Lithium reduces Alzheimer's disease pathology and stimulates hippocampal neurogenesis. Lithium promotes procognitive effects in patients with (prodromal) Alzheimer's disease. Low-dose lithium treatment promotes reduced Alzheimer's disease conversion rates. After 3 months of low-dose lithium treatment a slowing of cognitive decline is observed. Lithium might be a therapeutic option in the treatment of Alzheimer's disease. Abstract: Experimental data reveal that lithium is capable of attenuating Alzheimer's disease pathology and stimulating adult hippocampal neurogenesis. Clinical studies show procognitive effects in lithium-treated patients with amnestic MCI and Alzheimer's disease. These procognitive effects are associated with changes of CSF biomarkers of Alzheimer's disease. After 3 months of lithium treatment with low lithium levels, a slowing of cognitive decline is observed in patients with Alzheimer's disease. In patients with amnestic MCI with low-dose lithium treatment a trend of a reduced Alzheimer's disease conversion rate and longer cognitive stability was reported. Thus, lithium might be a therapeutic option in the treatment of Alzheimer's disease and its prodromal stages. But its therapeutic efficacy needs further evaluation. Further studies should include head-to-head comparisons with approved dementia treatment options. Due to lithium's therapeutic toxicity a thorough preselection of patients and a closely therapeutic monitoring is necessary. This manuscript is based on a literature review.